2009
DOI: 10.1002/lary.20130
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric pattern as a predictor of cardiovascular status: Development of a model for assessment of risk

Abstract: Audiogram pattern correlates strongly with cerebrovascular and peripheral arterial disease and may represent a screening test for those at risk. Patients with low-frequency hearing loss should be regarded as at risk for cardiovascular events, and appropriate referrals should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
100
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 37 publications
12
100
2
2
Order By: Relevance
“…In addition, older gerbils raised without exposure to noise or ototoxic drugs exhibit stria vascularis atrophy with pronounced capillary loss and a reduction in the endocochlear potential, which provides the voltage to the outer hair cells (cochlear amplifier) (Johnsson and Hawkins 1972;Pauler et al 1988;Schulte and Schmiedt 1992;Gratton et al 1996Gratton et al , 1997Thomopoulos et al 1997). Consistent with evidence for vessel disease affecting the stria vascularis, as well as the spiral ganglion (Makishima 1978), there is cross-sectional evidence that cardiovascular risk factors and vascular events are correlated with agerelated hearing loss (Susmano and Rosenbush 1988;Perez Villa et al 1995;Brant et al 1996;Friedland et al 2009). …”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In addition, older gerbils raised without exposure to noise or ototoxic drugs exhibit stria vascularis atrophy with pronounced capillary loss and a reduction in the endocochlear potential, which provides the voltage to the outer hair cells (cochlear amplifier) (Johnsson and Hawkins 1972;Pauler et al 1988;Schulte and Schmiedt 1992;Gratton et al 1996Gratton et al , 1997Thomopoulos et al 1997). Consistent with evidence for vessel disease affecting the stria vascularis, as well as the spiral ganglion (Makishima 1978), there is cross-sectional evidence that cardiovascular risk factors and vascular events are correlated with agerelated hearing loss (Susmano and Rosenbush 1988;Perez Villa et al 1995;Brant et al 1996;Friedland et al 2009). …”
Section: Introductionmentioning
confidence: 81%
“…In support of this premise, sclerosis of the internal auditory artery and circle of Willis was observed in a post-mortem examination of tissue from people who had age-related hearing loss and high blood pressure (Makishima 1978). In addition, a retrospective study of audiograms in patients with histories of vascular events demonstrated that people with flat and low sloping audiograms were significantly more likely to have had a cerebrovascular event than people with other audiometric profiles (Friedland et al 2009). …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have described microvascular disease as a possible mechanism for agerelated hearing loss 6,15 . This is the first large prospective epidemiologic human study of the association between cardiovascular risk factors and hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the vascular nature of the stria vascularis may make it especially vulnerable to vascular compromise 6 . Strial presbycusis, a distinct class of age-related hearing loss described by Schuknecht 7,8 , has been shown in cross-sectional analyses to be significantly associated with incident cardiovascular disease, with a demonstrated increased risk of stroke, coronary artery disease and myocardial infarction in individuals with this condition 6 . Nationally representative prevalence data have also indicated an increased prevalence of hearing loss in individuals with a history of hypertension, diabetes mellitus or smoking 2 .…”
Section: Introductionmentioning
confidence: 99%